Hypoparathyroidism-related health care utilization and expenditure during the first postoperative year after total thyroidectomy for cancer: a comprehensive national cohort study - Benmiloud, Fares; Le Bihan, Christine; Rebaudet, Stanislas; Marino, Patricia; Bousquet, Philippe-Jean; Bouée-Benhamiche, Elsa (Frontiers in Endocrinology, 2023)
Objectives: Hypoparathyroidism is the most common complication of total thyroidectomy for cancer, and requires calcium and/or vitamin D supplementation for an unpredictable period of time. The additional cost associated with this complication has not hitherto been assessed. The aim of this study was to assess the economic burden of postoperative hypoparathyroidism after total thyroidectomy for cancer in France. Methods: Based on the French national cancer cohort, which extracts data from the French National Health Data System (SNDS), all adult patients who underwent a total thyroidectomy for cancer in France between 2011 and 2015 were identified, and their healthcare resource use during the first postoperative year was compared according to whether they were treated postoperatively with calcium and/or vitamin D or not. Univariate and multivariate cost analyses were performed with the non-parametric Wilcoxon test and generalized linear model (gamma distribution and log link), respectively. Results: Among the 31,175 patients analyzed (75% female, median age: 52y), 13,247 (42%) started calcium and/or vitamin D supplementation within the first postoperative month (Group1), of which 2,855 patients (9.1%) remained treated at 1 year, while 17,928 patients (58%) were not supplemented within the first postoperative month (Group 2). Over the first postoperative year, mean overall and specific health expenditures were significantly higher for Group1 patients than for Group2 patients: €7,233 vs €6,934 per patient (p<0.0001) and €478.6 vs €332.7 per patient (p<0.0001), respectively. After adjusting for age, gender, Charlson Comorbidity index, ecological deprivation index, types of thyroid resection, lymph node dissection and complications, year and region, the incremental cost of overall health care utilization was €142 (p<0.004). Conclusion: Our study found a significant additional cost in respect of health expenditures for patients who had hypoparathyroidism after thyroidectomy for cancer, over the first postoperative year. Five-year follow-up is planned to assess the impact of more severe long-term complications on costs.